Qualitative study about the meanings of complementary and alternative medicine for cancer in students of health sciences (2018)
Social representations (SR) have always been a fundamental concept for psychology (Moscovici, 1973). This qualitative study uses the concept of SR, applied to the Health's field; the aim is to analyze the SR of Complementary and Alternative Medicine (CAM) for cancer in students of Health Sciences, using the methodology of thematic analysis. Results indicate that the SR of CAM have been developed based on many different elements, but where prevails an objectification and anchoring of CAM on what is common and familiar, rather than based on scientific knowledge. This to reflect on the training of future professionals and their practices in curing cancer. © 2018 Pontificia Universidad Javeriana.Las representaciones sociales (RS) han sido desde siempre un concepto fundamental para la psicología (Moscovici, 1973). El presente estudio cualitativo utiliza el concepto de RS aplicado al campo de la Salud, con el objetivo de analizar las RS de la Medicina Complementaria y Alternativa (MCA) para el cáncer, en estudiantes de Ciencias de la Salud, utilizando el análisis temático. Los resultados indican que las RS de la MCA se han elaborado con base en elementos muy diversos, pero donde prevale una objetivación y un anclaje de la MCA en lo que es común y familiar, más que en el conocimiento científico. Lo anterior para reflexionar sobre la formación de los futuros profesionales y sus prácticas en la cura del cáncer. © 2018 Pontificia Universidad Javeriana.